Synthesis of Multifunctional Nanoparticles for the Combination of Photodynamic Therapy and Immunotherapy - Mei-Hwa Lee; James L. Thomas; Jin-An Li; Jyun-Ren Chen; Tzong-Liu Wang; Hung-Yin Lin (MDPI AG, 2021)
Programmed death-ligand 1 protein (PD-L1) has been posited to have a major role in suppressing the immune system during pregnancy, tissue allografts, autoimmune disease and other diseases, such as hepatitis. Photodynamic therapy uses light and a photosensitizer to generate singlet oxygen, which causes cell death (phototoxicity). In this work, photosensitizers (such as merocyanine) were immobilized on the surface of magnetic nanoparticles. One peptide sequence from PD-L1 was used as the template and imprinted onto poly(ethylene-co-vinyl alcohol) to generate magnetic composite nanoparticles for the targeting of PD-L1 on tumor cells. These nanoparticles were characterized using dynamic light scattering, high-performance liquid chromatography, Brunauer-Emmett-Teller analysis and superconducting quantum interference magnetometry. Natural killer-92 cells were added to these composite nanoparticles, which were then incubated with human hepatoma (HepG2) cells and illuminated with visible light for various periods. The viability and apoptosis pathway of HepG2 were examined using a cell counting kit-8 and quantitative real-time polymerase chain reaction. Finally, treatment with composite nanoparticles and irradiation of light was performed using an animal xenograft model.